Which gay men would increase their frequency of HIV testing with home self-testing? - Bavinton, B.; Brown, Graham; Hurley, M.; Bradley, J.; Keen, P.; Conway, D.; Guy, R.; Grulich, A.; Prestage, G. (2013)
Many Australian gay men do not get tested for HIV at the recommended frequency. Barriers to HIV testing may be reduced by the availability of home HIV self-testing (HHST). An online cross-sectional questionnaire was conducted with 2,306 Australian gay men during 2009. Multivariate logistic regression identified factors associated with being likely to increase testing frequency if HHST was available, among previously-tested and never-tested men. Among 2,018 non-HIV-positive men, 83.9 % had been tested. Two-thirds indicated they would test more often if HHST was available irrespective of previous testing history. In multivariate analysis, independent predictors of increased testing frequency with HHST included preferences for more convenient testing, not having to see a doctor when testing and wanting immediate results among all men, as well as not being from an Anglo-Australian background and recent unprotected anal sex with casual partners among previously-tested men only. The majority of gay men report that being able to test themselves at home would increase their frequency of HIV testing. © 2013 Springer Science+Business Media New York.